A formação do caráter moral dos filhos : uma abordagem na perspectiva da ética das virtudes - Machado, Maria Carolina (My University, 2017)
The dissertation presents a study on the formation of children's moral character, considering especially the moral quality of parental relationships. The main questions are: a structured family and legislation that protects the rights of its members are sufficient to ensure a proper formation on the character of children in the virtues? Do parents' freedom and responsibility, when properly applyed on children obligation, ensure moral formation? The Aristotelian Ethics seems to offer theoretical support useful to understand and justify the formation on moral character of the children, which parents should enruse them. In order to answer these and other questions, it is necessary to analyze and interpret the changes that have occurred within the Brazilian family, emphasizing their moral, social and legal value in face of modern society; to address the importance of the family and its influence on the good formation of the children's character, considering the aspects of ethical action and the conception of Aristotelian happiness. In order to ensure the full development of moral virtues from childhood, especially in cases where parents submit their children to family conflicts, the presence of the law appears to be necessary, at least as a corrective to the action. However, the law itself may be deficient or even misunderstood by the agent, when the agent does not have a virtuous character, but the lack of the law, in many cases, may difficult the learning and the realization of the common well. Regardless of the family and social context, children's right to a proper character’s formation is a requirement that is independent of the law, which parents must achieve.
A dissertação apresenta um estudo sobre a formação do caráter moral dos filhos, levando-se em consideração, principalmente, a qualidade moral das relações parentais. As principais questões são: a família estruturada e a legislação que resguarda o direito de seus membros são suficientes para garantir uma adequada formação do caráter dos filhos nas virtudes? A liberdade e a responsabilidade dos pais, quando exercidas adequadamente nas obrigações para com os filhos, garante a formação moral? A Ética Aristotélica parece fornecer suporte teórico capaz de contribuir na compreensão e justificação da formação do caráter moral das crianças que os pais devem assegurar. Para responder a essas e outras questões é necessário analisar e interpretar as alterações ocorridas no âmbito da família brasileira, ressaltando o seu valor moral, social e jurídico perante a sociedade moderna; abordar a importância da família e sua influência na boa formação do caráter dos filhos, considerando os aspectos do agir ético e da concepção de felicidade aristotélica. Para garantir o pleno desenvolvimento das virtudes morais desde a infância, principalmente nos casos em que os pais submetem seus filhos a conflitos de natureza familiar, a presença da lei parece ser necessária, ao menos como corretivo da ação. No entanto, a lei sozinha pode se mostrar deficiente ou nem sequer compreendida pelo agente, quando este não tem um caráter virtuoso, mas a falta dela, em muitos casos, pode dificultar o aprendizado e a realização do bem comum. Independentemente do contexto familiar e social, o direito dos filhos a uma adequada formação do caráter é uma exigência que independe da lei e que os pais devem cumprir.
Keywords: Ética; Virtudes; Família; Caráter; Filosofia